Kemudahan dan Tantangan Green Banking di Era Digital dalam Penggunaan Marketplace - Indra Al Fitara; Muhammad Iqbal Fasa (Yayasan Literasi Sains Indonesia, 2025)
The concept of green banking is increasingly finding its relevance in the fast-paced digital era, especially through e-business platforms operating in the market. This study aims to understand how users, entrepreneurs, and other stakeholders perceive and interact with green banking practices in this digital context. The acceptance of green banking through e-business platforms offers various benefits, such as wider reach, cost efficiency, improved customer experience, better image, product innovation, and potential for new market growth. However, there are also challenges that need to be addressed, including digital security and trust issues, the digital divide, lack of green financial literacy, complexity of system integration, lack of standardization and regulation, and the risk of greenwashing. Therefore, this study will focus on the ease and complexity of implementing green banking in the digital era, especially in its integration into the market through e-business platforms. Furthermore, this study will also highlight existing and potential issues, such as limited consumer awareness, inadequate infrastructure, and challenges in implementing sustainable banking practices into the digital market system. By analyzing the perceptions and experiences of various parties, this study is expected to provide a comprehensive understanding of green banking practices in the digital market.